(untitled) (Third Sector Social Economic Review, 2017)
This research examines the factors that affect capital structure. For this purpose, the data of 60 firms listed on BİST-100 in Turkey between 2000 and 2012 have been analyzed. Analyses have been made separately for the firms grouped according to their asset values as big or small. Since the factors affecting capital structure are measured with more than one variable, so as detect most important factors, the forward selection method is used in which the variables are included one by one. While the factors effective on capital structure are asset structure, profitability, growth opportunities, the risk of the firm, non-debt tax shield; on the other hand considerable differences have been noticed between the factors affecting big and small firms’ total and long-term debts.